The Older, the More Forgiving? Characteristics of Forgiveness of Chinese Older Adults - Tao, Linjin; Zhu, Tingting; Min, Yanglu; Ji, Mingxia (Frontiers in Psychology, 2021)
The current study explored the characteristics of forgiveness in the aging cohorts which is regarded to be associated with healthy outcomes. Data were drawn from a sample of 308 older adults (aged from 60 to 98) who completed two forgiveness questionnaires: The Heartland Forgiveness Scale(HFS) and Tendency to Forgive Scale(TTF) to examine explicit forgiveness, and among the participants, 44 older adults were administrated on variant single category of implicit association test (SC-IAT) to examine the implicit forgiveness.The results revealed that (1) There is no correlation between explicit forgiveness and implicit forgiveness of the older adults. (2) The result of explicit forgiveness is relatively high with no significant age differences, while that of implicit forgiveness is relatively low with marginal significant age differences. (3) Gender differences are found in both explicit and implicit forgiveness . The findings indicated that (1) Explicit and implicit measures in this study have assessed different aspects of forgiveness tendency in older adults.(2) Implicit forgiveness falls behind explicit forgiveness and it is hard to achieve the true internal forgiveness in older adults according to data analysis.(3) There are no significant age differences in explicit forgiveness scores in older adults from this study. The level of explicit forgiveness in older adults is relatively stable. On the other hand, scores of implicit forgiveness are comparatively lower with significant age differences among the older adults.(4) Women’s scores were higher than men in explicit and implicit measures for forgiveness in this study.